Ornithine cyclodeaminase from octopine Ti plasmid Ach5: identification, DNA sequence, enzyme properties, and comparison with gene and enzyme from nopaline Ti plasmid C58. - Schindler, U (1989)
Octopine and nopaline are two arginine-derived opines synthesized in plant cells transformed with octopine or nopaline plasmids. Utilization in Agrobacterium tumefaciens is mediated by Ti plasmid regions called occ or noc (octopine or nopaline catabolism), and recent experiments showed that noc in pTiC58 codes for a pathway from nopaline to L-proline. The last enzyme is ornithine cyclodeaminase (OCD), an unusual protein converting L-ornithine directly into L-proline. We investigated whether octopine plasmid pTiAch5 also harbors a gene for OCD. The results revealed an ocd gene which is induced by octopine and maps in the occ region. DNA sequence analysis and comparison with the gene from pTiC58 showed that the two genes are related (69% homology in DNA and deduced amino acid sequence), and antiserum against OCD(C58) also reacted with OCD(Ach5). The enzyme activity was characterized, and a comparison with OCD(C58) showed that the properties are similar, but not identical. Differences were detected in the regulation of enzyme activity by L-arginine and L-proline and in the response to varying ratios of NAD+/NADH. It is proposed that this reflects different mechanisms for integration of opine catabolism into general metabolism.